METODOLOGIA PARA GESTÃO DE RISCOS EM ATIVIDADES QUE ENVOLVEM SEGURANÇA ELÉTRICA DE EQUIPES IN LOCO. - VIEIRA, Paula Alves Costa de Assis (2022)
The growing demand for electricity and the increasing levels of demand from consumers means that the regulation around the supply of energy is periodically reviewed, aiming at constant reductions in disturbances, which are changes in the conditions that characterize the operation of a system. electrical system outside the allowable variation range for its nominal values in the system. Unlike other sectors, the Electricity Sector is highly regulated, and a distributor cannot set its own prices, which must be the result of the tariff review process. Distributors, therefore, are better remunerated when they deliver quality energy to consumers and have lower operating expenses (OPEX). The difficulty in combining these two assumptions is that cost reduction involves, most of the time, a reduction in the number of employees, while improving supply requires more agile service and maintenance expenses. In this master's thesis work, a risk management methodology was developed that evaluated the impact of additional factors - such as fatigue, road condition and vegetation - on employee safety, analyzing the perception of risk, developing a matrix of additional risks and delivering solutions to mitigate such risks. For this purpose, own and outsourced employees from one of the 19 poles of a distributor answered a questionnaire, via Google Forms, about the frequency they are exposed to certain risks and the intensity of these risks, using the Likert scale, with responses from 1 to 5.A risk matrix with light and moderate risks was obtained, in which the largest number of responses focused on work with dense vegetation and end-of-life nets. At the same time, employees feel less secure in activities that require boats or motorcycles. It is concluded that security will be achieved through greater investments in network maintenance, lane cleaning and personnel (staff and training), in addition to previous analyzes by the Operations Center about the scenario (place and time) of service and support. of customer relationship areas.